An efficient provably-secure identity-based authentication scheme using bilinear pairings for Ad hoc network. (December 2017) - Wu, Libing; Wang, Jing; Raymond Choo, Kim-Kwang; Li, Yuangang; He, Debiao
Abstract: Designing an efficient and secure authentication scheme to ensure secure communication between parties in an ad hoc network remains challenging. Recently in 2017, Shaghayegh and Mehdi proposed an identity-based authentication scheme using bilinear pairings for Ad hoc networks. The scheme is claimed to be secure against a number of known attacks and provides non-repudiation property not found in most other authentication protocols. However, we demonstrate that their scheme is vulnerable to man-in-the-middle and forgery attacks, two previously unknown flaws. We then propose an improved mutual authentication scheme based on identity-based encryption (IBE) for Ad hoc networks. Our security analysis and experimental results demonstrate that the proposed scheme is secure and highly efficient.